MAPPING THE RELATIONSHIP OF ARTIFICIAL INTELLIGENCE TO THE FIELD OF PUBLIC RELATIONS AND RESEARCH TRENDS: BIBLIOMETRIC NETWORK ANALYSIS (Third Sector Social Economic Review, 2024)
Artificial intelligence is defined as an important technological advance that has led to radical changes in almost every sector in recent years. While these advances cause great change in the business world and society, they also create profound effects in the field of public relations. Artificial intelligence, including technologies such as data analysis, learning algorithms, and machine learning, enables more effective and efficient applications in areas such as big data analysis, automation, and personalization within public relations, thus impacting fundamental aspects of public relations. In this context, mapping the relationship between artificial intelligence and the field of public relations and the research trends of this relationship has become an important research topic. The study, conducted to map the relationship between artificial intelligence and the field of public relations, as well as the research trends in this area, included 64 articles from the Scopus database. In order to reveal the bibliometric aspects of the 64 publications included in the research, the R program (bibliometrix) and Biblioshiny, which serves as an interface to the R program for visualizations, were used. This analysis will reveal important connections and trends in the existing literature, helping us better understand the role of artificial intelligence technologies in public relations practices and guiding future studies.
Keywords: Artificial Intelligence; Public Relations; Artificial Intelligence and Public Relations Relation; Bibliometric Network Analysis